Removing cultural barriers to education: State-run religious schools and girls' education in Türkiye - Tolga Benzer (Aboa Centre for Economics (ACE), 2025)
This paper studies the impact of access to state-run religious schools on girls' outcomes in Türkiye. These schools, offering religious instruction and a conservative school environment, became accessible to girls following a 1976 court ruling. Exploiting variation in exposure to religious schools across district centers and cohorts, I find that access increased secondary school completion among girls-with more pronounced effects observed in conservative areas-while having negligible effects on boys. Treated women later had lower fertility and higher labor force participation. The findings show that removing cultural barriers to education can promote schooling and public life integration for culturally marginalized groups.
Keywords: I24; I25; J13; J16; J22; Z12; 330; Culture; Religion; Education; Women's Empowerment; Islam